PSYCHOLOGICAL FEATURES OF DEVELOPMENT OF CREATIVITY OF PERSONALITY - Poghosyan, S.G. (Modern Psychology, 2019)
The article discusses the issue of development of personality’s creativity with the help of special techniques. The use of which techniques in combination with personal qualities contributes to the development of creativity. We are analyzing the results of the study of personal qualities, creativity of undergraduates before and after the developing program. Technology development and creativity exercises gave the opportunity to go beyond the boundaries of the usual habitual, see new features, to experiment. Undergraduates have developed the flexibility of thinking, ease of association, ease of generating ideas, ability to use language creatively, elaborated tendency to problems of divergence type. The development program contributed to the development of criteria for creativity, such development was promoted by such personal qualities as courage, radicalism.
Keywords: creativity, personality, development, flexibility, originality.